The Establishment and Development of the Chinese Economic Legal System in the Past Sixty Years - Su, Chen (Columbia Journal of Asian Law, 2009)
Since the establishment of the People’s Republic of China (PRC) in 1949, the Chinese economic legal system has gone through multiple transformative stages, exhibiting different characteristics at each stage as a result of the interaction between the changing economic system and legal ideology of the time. Due to the differences between the prevailing economic systems and legal ideologies at different stages, the structural concepts, content, governing systems, implementation mechanisms and effects of the economic legal system vary significantly at each stage.